2008
DOI: 10.3201/eid1401.071315
|View full text |Cite
|
Sign up to set email alerts
|

International Circumpolar Surveillance System for Invasive Pneumococcal Disease, 1999–2005

Abstract: Disease rates are high among indigenous persons in Arctic countries, and PCV7 has resulted in decreased rates in North American children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 23 publications
4
48
2
1
Order By: Relevance
“…Men generally have a greater risk for pneumococcal diseases at all ages: both IPD (2,3,34) and CAP (17) are more common among men than women. The factors contributing to the greater susceptibility of men to IPD or CAP are not fully understood.…”
Section: Figmentioning
confidence: 99%
“…Men generally have a greater risk for pneumococcal diseases at all ages: both IPD (2,3,34) and CAP (17) are more common among men than women. The factors contributing to the greater susceptibility of men to IPD or CAP are not fully understood.…”
Section: Figmentioning
confidence: 99%
“…This investigation, together with data from Alaska that indicated that 78%-84% of invasive pneumococcal disease among children <2 years of age could be prevented by using PCV7, resulted in the implementation of vaccine programs in 3 northern regions of Canada using both the 23-valent polysaccharide vaccine and PCV7 in 2002. The introduction of PCV7 in the US Arctic (2001) and northern Canada (2002) has resulted in a rapid decrease in the proportion of isolates resistant to penicillin and other antimicrobial drugs, compared with the situation in countries not using the vaccine (Iceland and Finland) (34). Continued surveillance of invasive pneumococcal disease by ICS in these regions will monitor the impact and effectiveness of vaccine programs for preventing invasive pneumococcal disease and antimicrobial drug-resistant infections in these high-risk populations (34).…”
Section: Impact Of Icsmentioning
confidence: 99%
“…The introduction of PCV7 in the US Arctic (2001) and northern Canada (2002) has resulted in a rapid decrease in the proportion of isolates resistant to penicillin and other antimicrobial drugs, compared with the situation in countries not using the vaccine (Iceland and Finland) (34). Continued surveillance of invasive pneumococcal disease by ICS in these regions will monitor the impact and effectiveness of vaccine programs for preventing invasive pneumococcal disease and antimicrobial drug-resistant infections in these high-risk populations (34).…”
Section: Impact Of Icsmentioning
confidence: 99%
“…The International Circumpolar Surveillance (ICS) Program, an infectious disease surveillance network, was established in 1999 in Canada and the United States (Alaska) and initially focused on invasive pneumococcal disease, a leading cause of pneumonia and meningitis, especially among indigenous persons (2,10). In Alaska, prospective population-based surveillance data are collected by the Centers for Disease Control and Prevention's Arctic Investigations Program (AIP), which serves as the reference laboratory for Streptococcus pneumoniae for 23 hospitals in the state.…”
mentioning
confidence: 99%